Impact of artificial meat as novel food: controversies and future perspectives - Marco Cintoni; Marta Palombaro; Gabriele Egidi; Elena Leonardi; Federica Gardin; Gabriele Pulcini; Emanuele Rinninella; Pauline Raoul; Maria Cristina Mele (Nutrimentum et Curae)
Artificial meat, also called «synthetic», «cultured», or «in-vitro» meat, is growing in interest worldwide as a possible alternative protein source to regular meat derived from farm animals. Artificial meat production starts from an isolated muscle cell taken from a live animal and then cultivated to form slices of artificial meat with taste, texture, and look similar to regular meat. On the one hand, artificial meat can be considered safer since it is more uncontaminated from a microbiological point of view; on the other hand, the high level of cellular replication used in the production mechanisms can lead to a dysregulation of the DNA. While fats amount and type could be better than regular meat, protein intake may be the same, but iron and vitamin intake is still unclear. The impact on human health is poorly studied, and its impact on gut microbiota remains unknown. Moreover, the impact on the environment is still under debate. Well-designed studies are needed to evaluate better the impact of using artificial meat as a substitute for regular meat on human health, gut microbiota, and the environment.